SOFTWARE FOR ASSESSING THE QUALITY OF EDUCATIONAL INFORMATION SYSTEMS ON THE BASIS OF FUZZY KONETIVE MODELING - Sulyukova , Larisa; Kalandarov, Ilyos; Yorkulov , Bekhzod (Innovatsion texnologiyalar, 2023)
The paper considers the problem of assessing the quality of educational information systems (EIS) in the context of the digital transformation of society. An algorithm for determining the quality of information systems based on expert information is proposed. This approach differs in that it allows one to formalize qualitative assessments of the state of the system using the theory of fuzzy sets. The fuzzy quality assessment models included in the methodology, as well as the algorithms corresponding to them, allow, based on expert data, to assess the quality of educational information systems at the stage of their development, implementation and use. The implementation of the methodology makes it possible to increase the efficiency of the quality management process of educational information systems and the educational process as a whole. The article considers the use of a software package for the analysis and evaluation of the quality of educational information systems. The developed software product implements the following declared functions: assessment of the initial level of quality of the intellectual property; assessment of the possible level of quality of intellectual property in the event of attacks on the information resources of institutions.